Military law handbook for commanders - Kumar, Nilendra Major General (Universal Law Publishing Co.Pvt.Ltd, 2001)
The new edition of this book has taken into account a number of new changes. Setting up of the Armed Forces Tribunal has added an entirely new dimension to military discipline dispensation and service conditions governance. The Right to Information Act is now in place and makes commanders and designated officers responsible for supply of information